The association between smoking and clinical outcomes among spondylodesis patients: A systematic review and meta-analysis - Mahnoor Shafi; Anna Baukje Lebouille-Veldman; Chady Omara; Namita Kaler; John Kilgallon; Sulaiman Sajed; Linda S. Aglio; Rania A. Mekary; Carmen Vleggeert-Lankamp (PLoS ONE, 2026)
Background The effects of smoking on outcomes after spinal spondylodesis remain unclear due to conflicting findings in the existing literature. This meta-analysis aimed to evaluate the association between smoking and clinical as well as radiological outcomes following instrumented spinal fusion, and to examine differences based on smoking status, spinal region, and surgical extent. Methods PubMed, Embase, and Cochrane were searched up to August 2024 for comparative studies reporting outcomes in smokers and non-smokers undergoing spinal fusion. Extracted outcomes included clinical scores (Oswestry Disability Index [ODI], Neck Disability Index [NDI], Visual Analog Scale [VAS] for pain), fusion rates, pseudoarthrosis, and complications. Pooled percent mean change from baseline and weighted incidences with 95% confidence intervals (CI) were calculated using a random-effects model. Subgroup analyses were performed by spinal region, number of operated levels, and smoking history (current, former, never). Results Twenty-nine studies involving 6,687 patients were included. In most outcome measures, smokers showed smaller percent improvements than non-smokers. For instance, NDI improved by 42.8% (95% CI: 25.4–60.1%) in smokers vs. 49.7% (32.4–64.0%) in non-smokers; ODI improved by 48.6% (34.7–62.5%) vs. 56.5% (42.6–70.3%); and VAS back pain by 55.0% (29.7–80.2%) vs. 60.5% (35.2–85.7%). Fusion rates were lower in smokers (86.8%) than in non-smokers (95.1%), while pseudoarthrosis was more common in smokers (17.2% vs. 7.3%). Subgroup analyses revealed similar trends across spinal regions and surgical scope. A hierarchical pattern was observed, with never-smokers experiencing the most favorable outcomes, followed by former smokers. Conclusion In most instances, smokers appeared to experience worse outcomes following instrumented spinal procedures compared to non-smokers, and a hierarchical pattern was notable, with current smokers experiencing the worst outcomes, followed by former smokers compared to never-smokers. Future well-designed studies with proper adjustment for confounding are needed to further confirm these findings.